Chemical defoliation in rubber in Bahia State - Romano, Ronaldo; Rao, Sripathi (Pesquisa Agropecuaria Brasileira, 2014)
Chemical defoliation is a useful technique for inducing rubber trees to undergo an earlier and more uniform leaf shedding as has already been confirmed by experiments in South Bahia since 1980. It therefore has an important role in the control of leaf diseases. Three defoliants were used in the 1982 investigations: merphos by aerial spraying, MSMA by aerial spraying and ground spraying, thidiazuron by aerial spraying and fogging. The results show that, at the dosages used, spraying merphos or MSMA brought about good defoliation, while the former has the merit of being resistant to wash-off by ram, the latter is relatively cheap. Fogging thidiazuron gave satisfactory defoliation in an earlier experiment, but when applied at a lower dose in 1982, for economic reasons, it was unsuccessful. A few farms undertook chemical defoliation for the first time commercially on a small scale. The results were mixed. While it was satisfactory or good in some field, it was moderate or weak in others. This was attributed to delay in the treatment, and the presence of different ages of mature leaves in some fields.